Thermochromism from Ultrathin Colloidal Sb2Se3 Nanowires Undergoing Reversible Growth and Dissolution in an Amine–Thiol Mixture. Issue 4 (29th November 2018) - Wu, Wen‐Ya; Xu, Yang; Ong, Xuanwei; Bhatnagar, Sumit; Chan, Yinthai
Abstract: Liquid‐based thermochromics can be incorporated into an arbitrarily shaped container and provide a visual map of the temperature changes within its volume. However, photochemical degradation, narrow temperature range of operation, and the need for stringent encapsulation processes are challenges that can limit their widespread use. Here, a unique solution‐based thermochromic comprising ultrathin colloidal Sb2 Se3 nanowires in an amine–thiol mixture is introduced. The nanowires undergo reversible growth and dissolution with repeated cycles of heating and cooling between 20 and 160 °C, exhibiting intense and contrasting color changes during these processes. Furthermore, the transition temperature in which a change in color first appears can be continuously tuned over a range larger than 100 °C by introducing controlled amounts of Sn 2+ . The colloidal nanowire dispersion in the amine–thiol mixture retains its thermochromic properties over hundreds of temperature cycles, continuous heating at 80 °C over months, and shelf life of up to 2 years in an open container under ambient conditions. To illustrate its utility as a robust liquid thermochromic, the nanowire solution is coated onto standard filter paper and its uses as a rewritable surface by thermal scribing, as well as an inexpensive means of visualizing the temperature distribution of an anisotropically heated block are demonstrated. Abstract : The reversible growth/dissolution of colloidal semiconductor nanowires in an amine–thiol mixture as a function of heating/cooling, which is accompanied by contrasting color changes, serves as the basis for solution‐based thermochromics. Coating the mixture onto standard filter paper yields a re‐writable surface via thermal scribing, as well as an inexpensive means of visualizing the temperature distribution of a heated surface.